Impact of Arsenic Related Defects on Electronic Performance of ZrO2/GaAs: Density Functional Theory Calculations. (14th January 2015) - Wang, Yu-Peng; Wang, Yong-Ping; Shi, Li-Bin
Abstract: Arsenic can diffuse into high-κ dielectrics during GaAs-based metal oxide semiconductor transistor process, which causes the degradation of gate dielectrics. To explore the origins of the degradation, we employ nonlocal B3LYP hybrid functional to study arsenic related defects in ZrO2 . Via band alignments between the GaAs and ZrO2, we are able to determine the defect formation energy in the GaAs relative to the ZrO2 band gap and assess how they will affect the device performance. Arsenic at the interstitial site serves as a source of positive fixed charge while at the oxygen or zirconium substitutional site changes its charge state within the band gap of GaAs. Moreover, it is found that arsenic related defects produce conduction band offset reduction and gap states, which will increase the gate leakage current.